Factors Determining Survival and Retention among HIV-Infected Children and Adolescents in a Community Home-Based Care and a Facility-Based Family-Centred Approach in Kampala, Uganda: A Cohort Study. (1st April 2014) - Massavon, W.; Barlow-Mosha, L.; Mugenyi, L.; McFarland, W.; Gray, G.; Lundin, R.; Costenaro, P.; Nannyonga, M. M.; Penazzato, M.; Bagenda, D.; Namisi, C. P.; Wabwire, D.; et al.
Abstract : We describe factors determining retention and survival among HIV-infected children and adolescents engaged in two health care delivery models in Kampala, Uganda: one is a community home-based care (CHBC) and the other is a facility-based family-centred approach (FBFCA). This retrospective cohort study reviewed records from children aged from 0 to 18 years engaged in the two models from 2003 to 2010 focussing on retention/loss to follow-up, mortality, use of antiretroviral therapy (ART), and clinical characteristics. Kaplan Meier survival curves with log rank tests were used to describe and compare retention and survival. Overall, 1, 623 children were included, 90.0% (1460/1623) from the CHBC. Children completed an average of 4.2 years of follow-up (maximum 7.7 years). Median age was 53 (IQR: 11–109) months at enrolment. In the CHBC, retention differed significantly between patients on ART and those not (log-rank test, adjusted, P < 0.001 ). Comparing ART patients in both models, there was no significant difference in long-term survival (log-rank test, P = 0.308, adjusted, P = 0.489 ), while retention was higher in the CHBC: 94.8% versus 84.7% in the FBFCA (log-rank test, P < 0.001, adjustedP = 0.006 ). Irrespective of model of care, children receiving ART had better retention in care and survival.